RESEARCH OF INTERCOMMUNICATION IS BETWEEN LEVEL OF TOXICITY AND COMPONENT STRUCTURE OF SEWAGE - ГРИЦЕНКО, А. В.; КРАЙНЮКОВ, А. М. (Man and Environment. Issues of Neoecology, 1970)
For research of intercommunication between the levels of toxicness and muddiness of water were drawn on the results of measuring of component composition and determination of toxicness of sewages of enterprises of the different industries of economy, located on territory of a few areas of Ukraine.It is shown that in each of cases the set of meaningful physical and chemical indexes which correlate with data of biotesting is different and depends on component composition of sewages. The brought results over are base on the use of far of experimental data and have an important practical value for the exposure of reasons of origin of toxic properties of sewages with the purpose of realization of corresponding nature protection measures on their removal.